Unmet Supportive Care Needs of General Cancer in Kurdistan Region- Iraq - Ezaddin Kamal Mahmod 1, Saadia Ahmed Khuder2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: Cancer is a class of diseases or disorders characterized by uncontrolled division of cells. Objective: The study aims to to determine the SCNs of cancer patients in Iraq. Methodology: The present cross-sectional study and data was conducted in Rezgary teaching and Nankaly Oncology Hospital in the Kurdistan Federal Region of Iraq. A total of 300 eligible cancer patients were invited to participate in the study from February to August, 2018. Eligibility criteria included: 18 years or above; having a defifinite diagnosis of any type of cancer; physically or mentally able to participate in the study; and being aware of exact diagnosis for at least three months. Results: In 15 items of the SCNs, more than 60% of the participants reported that their needs were unmet. Most frequently, unmet needs were related to health system and information, physical and daily living, psychological, and patient care and support domains, and most met needs were related to physical and daily activity domains. Conclusions: Kurdish cancer patients had many unmet needs and there is a need for establishing additional supportive care services and educational programs to increase quality of life in Kurdistan Region- Iraq.